2009
DOI: 10.1159/000203346
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Mild Cognitive Impairment Revisited after One Year

Abstract: Background/Aims: The diagnostic stability of mild cognitive impairment (MCI) on short-term follow-up is a key issue in the characterization of this clinical syndrome. We aim to determine the cognitive outcome after 1 year of follow-up in a cohort of older adults. Methods: Baseline clinical and neuropsychological assessments were carried out in older subjects recruited at a tertiary memory clinic. The subjects were reassessed after 1 year of follow-up with the same clinical and neuropsychological protocol. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 77 publications
2
28
0
3
Order By: Relevance
“…However, in a follow-up study, Tabert et al (2006) found that 38 out of 39 patients that converted to AD had a baseline diagnosis of a-md-MCI, while none of them had a baseline diagnosis of a-sd-MCI. Diniz et al (2009) found that those MCI who progress to dementia showed a worse global cognitive performance and multiple cognitive deficits at baseline than those MCI who remained stable. Similarly, Han et al (2012) reported that the rate of progression to dementia in a-sd-MCI patients was very similar to the rate of reversion to the normal cognition, while in the a-md-MCI group, the rate of conversion to dementia was significantly higher when compared to the rate of reversion.…”
Section: Discussionmentioning
confidence: 95%
“…However, in a follow-up study, Tabert et al (2006) found that 38 out of 39 patients that converted to AD had a baseline diagnosis of a-md-MCI, while none of them had a baseline diagnosis of a-sd-MCI. Diniz et al (2009) found that those MCI who progress to dementia showed a worse global cognitive performance and multiple cognitive deficits at baseline than those MCI who remained stable. Similarly, Han et al (2012) reported that the rate of progression to dementia in a-sd-MCI patients was very similar to the rate of reversion to the normal cognition, while in the a-md-MCI group, the rate of conversion to dementia was significantly higher when compared to the rate of reversion.…”
Section: Discussionmentioning
confidence: 95%
“…52,53 In a longitudinal study carried out by our group, we found that 22% of patients initially diagnosed as MCI resumed normal cognitive function after 1 year of follow-up. 54 When the specific MCI subtype was taken into account, 37.5% of amnestic MCI subjects resumed normal cognitive function, as opposed to 12% of subjects with multiple-domain MCI and 14% of those with non-amnestic MCI. In this study, the best predictors of diagnostic instability were younger age and better global cognitive performance at baseline.…”
Section: Longitudinal Studies and MCI Prognosismentioning
confidence: 99%
“…S4). Several reasons may account for this decrease: whether and when aMCI patients convert to AD are uncertain [4,7,[54][55][56] ; the AD patients in the present study were at a relatively mild stage (25 patients CDR = 1; 10 patients CDR = 2), which indicated an overlap in greymatter atrophy between the AD and aMCI groups (Fig. 2); and the pathological changes that underlie cognitive loss in patients with AD might emerge 10-20 years before symptoms of dementia [57] , implying that some of the NCs might have been in the preclinical stage of AD.…”
Section: Is Grey-matter Atrophy Useful For Distinguishing Between Ad mentioning
confidence: 99%